Plasma Proteomic Markers of Interleukin-1β Pathway Associated with Incident Age-Related Macular Degeneration in Persons with AIDS - Peter W. Hunt, MD; Adam B. Olshen, PhD; Natalia Murad, PhD; Gabrielle C. Ambayec, BS; Efe Sezgin, PhD; Michael F. Schneider, MS; Douglas A. Jabs, MD, MBA (Ophthalmology Science)
Objective: To evaluate the associations of plasma inflammatory proteins with age-related macular degeneration (AMD) in persons with the AIDS, using a discovery-based proteomics approach. Design: A nested case-control study (analysis 1) and nested cohort study (analysis 2). Participants: Persons with AIDS enrolled in the Longitudinal Study of the Ocular Complications with AIDS (LSOCA). Methods: Cryopreserved plasma specimens obtained at baseline were assayed for inflammatory proteins using the Olink Inflammation Explore Panel 1. In analysis 1, baseline proteomic profiles for 26 persons with AIDS and incident intermediate-stage AMD 5 to 10 years after baseline and 49 matched controls (matched for age, biologic sex, race/ethnicity, and follow-up) without AMD were compared. In analysis 2, 475 persons from LSOCA with baseline plasma inflammatory proteomic profile measurements were followed for incident cataract and mortality. Main Outcome Measures: Incident intermediate-stage AMD; incident cataract; and mortality. Results: Of 365 measurable plasma inflammatory proteins, 118 (32%) were associated with incident intermediate-stage AMD at the false discovery rate-adjusted Q < 0.05 level after adjustment for smoking, CD4+ T count, and plasma human immunodeficiency virus RNA level. Gene ontology pathway enrichment analysis identified the interleukin (IL)-1β pathway and wound healing pathways, including tissue inhibitor of metalloproteinase 3, as significantly associated with incident AMD. These associations were qualitatively different from those associated with incident cataracts, where elevated levels of inflammatory proteins were associated with a decreased risk of cataracts. A much broader number of inflammatory pathways, including those related to the adaptive immune system, were associated with mortality. Conclusions: Upregulation of the IL-1β pathway appears to be associated with an increased risk of incident AMD in persons with AIDS. Given the availability of inhibitors of this pathway, inhibition of the IL-1β pathway may provide a therapeutic avenue for treatment of AMD. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.